Studi Tentang Pendidikan Keluarga Dalam Tinjauan Hadis Nabi - Nurdiana Sari (MKKS SMA, MKKS SMP se-Kota Metro, Persatuan Sarjana Pendidikan Islam Wilayah Provinsi Lampung, dan CV.IQRO Penerbitan, 2020)
The family is the smallest component in a nation. If in the nation there is only one family that is weak or damaged then the nation will be weak too. Children are part of a family that really needs guidance from both parents. The guidance includes: fostering the soul of parents, fostering monotheism for children, fostering faith in children and social coaching for children. People who neglect their children's education, do not pay attention to their teachings, instead open the door of their hearts to always love the world and submit to their rule, so that the children disobey them and do not follow the instructions of their teachings, so let him not blame anyone other than himself. Losses always befall people who are negligent and negligent. In this day and age, too many children who are disobedient and do not want to hear the words of their parents are scattered everywhere. If we examine carefully, the cause is none other than the negligence of the parents who have neglected the care of the children since childhood.